The geology, alteration, and mineralization of the Turquoise Lake area, Lake County, Colorado - Craig, Steven D., author; Thompson, Tommy B., advisor; Greybill, F., committee member; Burns, L. K., committee member (Colorado State University. Libraries, 1980)
The Turquoise Lake intrusive complex is located on the northeast flank of the Sawatch Range in Lake County, Colorado. The complex is centered on a 35 million year old subvolcanic stock of quartz latite porphyry. The intrusive rocks associated with the explosive emplacement of the stock includes an intensely brecciated border phase surrounding the porphyritic stock center, and dikes of similar composition. Other Oligocene intrusives include early dikes of latite and lake dikes o f rhyolite. North-trending structures reflecting the axis of the Sawatch Range are common throughout the Turquoise Lake area. The Central Fault, a major north-trending fault, is thought to have localized the stock at the juncture with inferred east-west trending structures. Radial faulting found in the Sugarloaf and St. Kevin Mining Districts formed during the emplacement of the Turquoise Lake stock. Widespread and pervasive alteration halos including a propylitic zone, transition zone, phyllic zone, and quartz-topaz subzone are centered on the stock. A late kaolinite-sericite zone is found at depth within the stock or in late dikes found above this zone. Pervasive disseminated pyrite is found increasing up to 10 volume percent toward the stock. Molybdenite is found in the quartz -topaz subzone and in quartz veinlets outside this area. The rocks surrounding the Turquoise Lake stock are geochemically anomalous in Cu, Mo, Ph, Zn, Sn, W and F. These elements form donut shaped dispersion halos centered on the stock. Two pulses of mineralization are inferred with double halos by the elements Cu, Pb, and Zn. Drillhole geochemistry finds Mo, Cu, and W displaying discrete halo boundaries and increasing values toward the bottom of the holes. Studies of vein mineralogy relationships from the St. Kevin and Sugarloaf Districts find four episodes of mineralization. These include an early ore preparation stage, main ore stage, late ore stage, and supergene stage. The bulk vein mineralogy consists of a quartz gangue, pyrite, galena, sphalerite, and chalcopyrite. Samples from different locations throughout the mining districts were analyzed for Cu, Mo, Pb, Zn, Ag, Sn, W, and Bi. These metals formed distinct concentration halos spatially associated with the Turquoise Lake stock. The Turquoise Lake stock has many features associated with known molybdenite ore bodies. These features suggest that potential exists for discovery of a molybdenite ore body at Turquoise Lake.
Keywords: Geology -- Colorado -- Lake County; Mines and mineral resources -- Colorado -- Lake County